2012
DOI: 10.1007/s00253-012-4454-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rhamnolipids produced by wild-type and engineered Burkholderia kururiensis

Abstract: Biosurfactants are a class of functional molecules produced and secreted by microorganisms, which play important roles in cell physiology such as flagellum-dependent or -independent bacterial spreading, cell signaling, and biofilm formation. They are amphipathic compounds and comprise a variety of chemical structures, including rhamnolipids, typically produced by Pseudomonas spp. and also reported within other bacterial genera. The present study is focused on Burkholderia kururiensis KP23(T), a trichloroethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 47 publications
0
49
0
1
Order By: Relevance
“…chlororaphis NRRL B-30761 is the first reported wildtype nonpathogenic organism that solely produces R 1 L (Gunther et al 2005(Gunther et al , 2007. Other reported RL-producing wild-type bacteria, including the non-Pseudomonas species (Hošková et al 2013;Řezanka et al 2011;Tavares et al 2013), synthesize a mixture of R 1 L and R 2 L. Therefore, in the present study, we genetically engineer the nonpathogenic NRRL B-30761 into an R 2 L-producing strain by expressing a heterologous rhlC gene in the organism. The resultant recombinant, P. chlororahis [pBS29-P2-rhlC], was shown to produce R 2 L at a level that is 2.4 times higher than R 1 L ( Table 2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…chlororaphis NRRL B-30761 is the first reported wildtype nonpathogenic organism that solely produces R 1 L (Gunther et al 2005(Gunther et al , 2007. Other reported RL-producing wild-type bacteria, including the non-Pseudomonas species (Hošková et al 2013;Řezanka et al 2011;Tavares et al 2013), synthesize a mixture of R 1 L and R 2 L. Therefore, in the present study, we genetically engineer the nonpathogenic NRRL B-30761 into an R 2 L-producing strain by expressing a heterologous rhlC gene in the organism. The resultant recombinant, P. chlororahis [pBS29-P2-rhlC], was shown to produce R 2 L at a level that is 2.4 times higher than R 1 L ( Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…Rhamnolipids (RLs) are a family of rhamnose-containing glycolipids first characterized in Pseudomonas aeruginosa (Jarvis and Johnson 1949) and had since been described in other bacteria (Gunther et al 2005(Gunther et al , 2007Řezanka et al 2011;Tavares et al 2013;Toribio et al 2010). The lipid portion of most RLs consists of 3-hydroxyalkanoyl-3-hydroxyalkanoate (C x -C y , where x and y are the carbon chain lengths of the alkanoate) moiety, though some may contain only a monomeric 3-hydroxyalkanoate.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenicity of biosurfactant producers is key factor to prevent large-scale production; therefore, the nonpathogenic eco-friendly organisms need to be explored further, and a library of collections is important for the future development in this area of study. Tavares et al ( 2013 ) …”
Section: Resultsmentioning
confidence: 97%
“…Rhamnolipids produced by the engineered strains were mainly mono-RL as opposed to wild-type strains B. kururiensis and P. aeruginosa that predominantly produce di-RLs. This organism is a promising biosurfactant producer with potential environmental and biotechnological application especially due to its nonpathogenicity and compatibility with metabolic engineering procedures (Tavares et al 2013 ).…”
Section: Production Of Biosurfactant By Recombinant Strainsmentioning
confidence: 99%
“…In recent years, several studies have shown that a number of Burkholderia species such as Burkholderia thailandensis [34,35], Burkholderia glumae [36], Burkholderia kururiensis [37], Burkholderia plantarii [38], and Burkholderia gladioli [39] were able to produce biosurfactant. However, the ability of Burkholderia cepacia to produce a biosurfactant was not sufficiently documented in the literature.…”
Section: Discussionmentioning
confidence: 99%